2019
DOI: 10.3390/condmat4030065
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigations of Single Metal Atoms (Sc, Ti, V, Cr, Mn, and Ni) Embedded in Hexagonal Boron Nitride Nanosheets for the Catalysis of CO Oxidation

Abstract: We evaluated isolated transition metal atoms (Sc, Ti, V, Cr, Mn, and Ni) embedded in hexagonal-BN as novel single atom catalysts for CO oxidation. We predicted that embedded Ni atoms should have superior performance for this task. Ti, V, and Mn bind CO2 too strongly and so the reaction will not proceed smoothly. We studied the detailed reaction processes for Sc, Cr, and Ni. The Langmuir–Hinshelwood (LH), Eley–Rideal (ER), and the new termolecular Eley–Rideal (TER) processes for CO oxidation were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…Although h‐BN‐supported single atoms have not been reported experimentally, researchers have computationally examined them for catalytic reactions, such as CO oxidation [13–18] . More interestingly, Zhao and Chen predicted that h‐BN‐supported Mo single atom is a potential catalyst for electrocatalytic N 2 reduction, [19] while Deng et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although h‐BN‐supported single atoms have not been reported experimentally, researchers have computationally examined them for catalytic reactions, such as CO oxidation [13–18] . More interestingly, Zhao and Chen predicted that h‐BN‐supported Mo single atom is a potential catalyst for electrocatalytic N 2 reduction, [19] while Deng et al.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Although h-BN-supported single atoms have not been reported experimentally, researchers have computationally examined them for catalytic reactions, such as CO oxidation. [13][14][15][16][17][18] More interestingly, Zhao and Chen predicted that h-BN-supported Mo single atom is a potential catalyst for electrocatalytic N 2 reduction, [19] while Deng et al suggested that Co embedded in h-BN may be promising for oxygen reduction reaction. [20] One thing to note is that these studies focused on only the B vacancy, but N vacancy has been observed experimentally in h-BN as well.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40] Furthermore, 2D materials have become an important platform to design numerous single-atom catalysts for diverse chemical reactions, such as N 2 reduction, CO 2 reduction, and CO oxidation. [41][42][43][44][45][46][47][48][49][50][51][52] The ease of isolation and separation of the heterogeneous catalysts from the desired organic product and the recyclability and reusability further enhanced the sustainability of the catalysts. [53][54][55][56][57][58][59][60] Moreover, the heterogeneous catalysts not only catalyze the reactions on their own, but also serve as an effective support for the immobilization of active catalysts and facilitate the efficient magnetic separation of the catalysts for their recovery and reusability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, graphene and graphene-like materials have been used as templates for the synthesis of different noble-metal composites, providing a great performance in electrocatalytic applications, such as carbon dioxide (CO ) reduction and hydrogen evolution reaction [ 12 ]. Numerous computational and experiments were performed to study and evaluate the adsorption characteristics of graphene and graphene-like metals (see, for example, in [ 4 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]), but there are few works in this area that have used mathematical modeling, and new mathematical models are needed to secure the full import of nanotechnology into this area. Therefore, we used mathematical modeling techniques that are necessary to formulate explicit analytical criteria and ideal model behaviour to complement the efforts of experimentalists.…”
Section: Introductionmentioning
confidence: 99%